Mental health problems, benefits and tackling discrimination. (6th July 2018) - Galloway, Alexander; Boland, Billy; Williams, Gareth
Summary: Poverty is strongly associated with mental illness. Access to state benefits can be a lifeline for people with mental health problems in times of hardship and can assist them on their journey of recovery. However, benefit application processes can discriminate against those with mental illness and can result in individuals unjustly missing out on support. Clinical evidence from mental health professionals can ameliorate these challenges and ensure that people get access to financial help. Declaration of interest: Dr Billy Boland is on the advisory board of the Money and Mental Health Policy Institute.